1975
DOI: 10.1152/ajplegacy.1975.228.4.1276
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynimic effects of systemic and central administration of clonidine in the monkey

Abstract: Systemic and regional hemodynamic changes were measured in restrained, conscious rhesus monkeys with indwelling arterial and venous catheters before and after clonidine (5 and 15 mug/kg) was slowly infused intravenously or smaller doses (2 mug/kg) were injected into a lateral cerebral ventricle. Dye-dilution cardiac outputs and the complete distribution of cardiac output were obtained intermittently with the use of the radioactive microsphere method. After the higher intravenous dose and the intraventricular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(1974) did not find a decrease in splanchnic blood flow in rats. Hepatic blood flow has been found to be increased in monkeys after intravenous or intracerebroventricular administration of clonidine (BOLME et a!., 1975).…”
Section: N Renal Blood Flowmentioning
confidence: 99%
“…(1974) did not find a decrease in splanchnic blood flow in rats. Hepatic blood flow has been found to be increased in monkeys after intravenous or intracerebroventricular administration of clonidine (BOLME et a!., 1975).…”
Section: N Renal Blood Flowmentioning
confidence: 99%
“…Most investigations have been done on animals and have reported the renal effects of short-term clonidine administration. In a short-term study in monkeys, Bolme et al 5 reported a decrease in blood flow to skin and skeletal muscle with maintenance of circulation to the hepatic and renal arteries during the first hour. Clonidine induced a decline in RBF in dogs with renal hypertension.…”
Section: Discussionmentioning
confidence: 99%